Devising a method for dynamic stabilization of PoS consensus using adaptive weight mixing and a time factor - Solomka, Ihor; Liubinskyi, Bohdan (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process of validator committee selection in permissionless blockchain networks operating on the Proof-of-Stake algorithm. The task addressed relates to the vulnerability of conventional static selection schemes to identity-forging (Sybil) attacks. A fixed baseline weight facilitates stake splitting among numerous fictitious entities, allowing attackers to gain control over the network. In response to these challenges, a method for the dynamic stabilization of consensus based on an adaptive control law has been devised. This method automatically regulates the weight mixing intensity using the smoothed Gini coefficient. The concept of Proof-of-Persistence has been proposed, which replaces the uniform baseline distribution with a time-weighted reputation of the participants. The analytical and experimental analyses of data from 10 real-world networks were conducted, demonstrating that the proposed mechanism reliably reduces the aggregate weight of a potential attacker. The result is attributed to the fact that when new entities are created, their prior participation experience is not considered, and the loss of reputational weight outweighs the benefits of acquiring new baseline shares. This makes the stake-splitting strategy economically unviable. An important distinct feature is that the system's adaptation is carried out exclusively on the basis of deterministic on-chain data, without the need for external identification. The proposed system functions autonomously: under a normal mode, intervention is minimized, while under the risk of an oligopoly, protection is strengthened. The results could be practically applied to the architecture of permissionless blockchain networks as the method might be integrated both at the network protocol core level and in the form of smart contracts to enhance the security of distributed ledgers without additional manual adjustments.